Journalism as a democratic art : selected essays - Campbell, Cole C. (Kettering Foundation Press, 2012)
In this book, Cole C. Campbell invites the reader to join him in imagining how journalism might facilitate a more vibrant democracy. "What if we reoriented our journalism away from the sources of news and toward to the recipients of news?" he asks. It is a question intended to redirect the focus on how elected officials and technical experts define the problems and purpose to solve them. Rather, it positions citizens working in communities as experts in their own lives and agents in the naming and solving of their own problems. "Public journalism" which Campbell defines, describes, and defends in these essays, positions journalists as stewards of this process.